MEKANISME CHECK AND BALANCES DALAM PENERBITAN UNDANG-UNDANG NOMOR 2 TAHUN 2020 TENTANG KEBIJAKAN KEUANGAN DAN STABILITAS SISTEM KEUANGAN UNTUK PENANGANAN PANDEMI CORONA VIRUS DIS-EASE 2019 (COVID- 19) DAN/ATAU DALAM RANGKA MENGHADAPI AN-CAMAN YANG MEMBAHAYAKAN PEREKONOMIAN NASIONAL DAN/ATAU STABILITAS SISTEM KEUANGAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia adheres to the separation of power system and adheres to the Trias politica un-derstanding, where the government system is divided into 3 rooms, legislative, executive and judicial, each of which carries out its duties and functions with a mechanism of checks and bal-ances both in normal and abnormal conditions (state of emergency). Covid-19 which became a world epidemic attacked and affected the state of a country, until Indonesia with the authority given to the 1945 Constitution to the Executive in this case the President to deal with crises and emergencies by issuing a government regulation in lieu of Law Number 1 of 2020 concerning financial policy, where it is hoped that this Government Regulation in Lieu of Law will be able to overcome the economic crisis and become a legal umbrella in terms of diverting APBN funds for the benefit of health recovery and economic recovery. The formulation of the problem pro-posed is how the mechanism of checks and balances against the government in the issuance of Law Number 2 of 2020 regarding financial policy and what is the compelling urgency in the background of the government Regulation in Lieu of Law Number 1 of 2020 concerning finan-cial policy in terms of the decision of the Constitutional Court Number 138 of 2009.This research is a normative juridical research, research conducted based on legal materials and legislation. The approach taken is close to the library approach, namely by studying books and legislation. The types of data used are primary data types, secondary data sources, namely data sources derived from books and other regulations.The theory used in this research is the theory of Trias Politica and the theory of Emergency Constitutional Law. From the research results, the trias politica theory requires a clear separation of powers in order to prevent centralized power and the issuance of government regulation in lieu of Law Number 1 of 2020 concerning financial policy into Law Number 2 of 2020 concern-ing financial policy. the important roles and tasks of the legislature, especially in terms of budg-eting or budgeting tasks with the argument to facilitate policy directions in dealing with the co-rona pandemic. And the president takes refuge in the provisions of the 1945 Constitution Article 22 paragraph (1) it is stated that in matters of urgency that force the president to have the right to stipulate government regulations in lieu of the law. This study also conducted a study on whether the issuance of this Government Regulation in Lieu of Law Number 1 of 2020 fulfilled the ele-ment of compelling urgency in accordance with the provisions of the Constitutional Court's deci-sion Number 138 of 2009.Keywords: Government regulation in lieu of law Number 1 of 2020, Trias Politica, Checks and balances, Coercive Crisis.